1996
DOI: 10.1029/96ja02221
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic radiation in the heliosphere at successive solar minima: 3. Steady state drift solutions of the transport equation

Abstract: Cosmic ray intensities and density gradients, as observed by the Pioneer 10 and 11, Voyager 1 and 2, and IMP 8 spacecraft during the 1977 and 1987 solar minimum periods, are interpreted in terms of a two‐dimensional version of the cosmic ray transport equation that includes drifts. This paper is a follow‐up of an earlier no‐drift version to elucidate the necessity and limitations of drift effects as demanded by actual observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…This gives different diffusion coefficients for alternate solar cycles in qualitative agreement with Reinecke et al (1996) and Potgieter (2000), who found that these coefficients were different for consecutive solar minimum periods. This might also indicate that an additional charge-sign dependent mechanism could be contributing to modulation such as magnetic helicity (e.g.…”
Section: Model and Parameterssupporting
confidence: 71%
“…This gives different diffusion coefficients for alternate solar cycles in qualitative agreement with Reinecke et al (1996) and Potgieter (2000), who found that these coefficients were different for consecutive solar minimum periods. This might also indicate that an additional charge-sign dependent mechanism could be contributing to modulation such as magnetic helicity (e.g.…”
Section: Model and Parameterssupporting
confidence: 71%
“…This new spectrum may call for the repetition of some previous work. Reinecke et al [1993Reinecke et al [ , 1996, for instance, performed modulation calculations on ACRs, but they guessed what the input spectra might be, without having a physical model.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that different diffusion coefficients can be assumed for different polarity cycles (e.g. Reinecke, Moraal, and McDonald, 1996;Burger, Potgieter, and Heber, 2000;Potgieter, 2000; to improve compatibility with the observations. However, C 1 = 3.0 and C 2 = 0.8 are considered as the overall best compatible scenario.…”
Section: Effect Of Different C 1 and C 2 Valuesmentioning
confidence: 99%